2020
DOI: 10.1038/s41598-020-74546-3
|View full text |Cite
|
Sign up to set email alerts
|

A national database analysis for factors associated with thyroid cancer occurrence

Abstract: In order to analyze the associations between thyroid cancer and environmental factors, we analyzed the national sample cohort representative of the entire population provided by the Korean National Health Insurance Service database record from 2006 to 2015. The cohort was categorized according to age, body mass index, income, residential areas, frequency of exercise, frequency of alcohol drinking, diet, presence or absence of hyperthyroidism, presence or absence of hypothyroidism, and smoking data. Age ≥ 55 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…TSI can also stimulate angiogenesis, promote tumor development, and make tumors more aggressive (6). Previous studies have shown that the risk of DTC in patients with hyperthyroidism is 6.8 times higher than that in patients with normal thyroid function and that the longer the duration of hyperthyroidism is, the greater the risk of DTC and the worse the clinicopathological characteristics and prognosis (7)(8)(9)(10). In this study, the course of hyperthyroidism did not affect the efficacy of 131 I (P=0.441, U=834.00), but patients who received preoperative drug treatment for hyperthyroidism were more likely to achieve ER (P=0.005, χ 2 =10.62).…”
Section: Discussionmentioning
confidence: 99%
“…TSI can also stimulate angiogenesis, promote tumor development, and make tumors more aggressive (6). Previous studies have shown that the risk of DTC in patients with hyperthyroidism is 6.8 times higher than that in patients with normal thyroid function and that the longer the duration of hyperthyroidism is, the greater the risk of DTC and the worse the clinicopathological characteristics and prognosis (7)(8)(9)(10). In this study, the course of hyperthyroidism did not affect the efficacy of 131 I (P=0.441, U=834.00), but patients who received preoperative drug treatment for hyperthyroidism were more likely to achieve ER (P=0.005, χ 2 =10.62).…”
Section: Discussionmentioning
confidence: 99%
“…The known risk factors for TC include female sex, obesity, smoking status, radioactive iodine exposure history, and family genetic history ( 86 88 ). However, these recognized causative factors do not fully explain the increasing incidence of TC.…”
Section: Discussionmentioning
confidence: 99%
“…Incidences of TC are most common among younger adults [ 14 , 15 ]. Women are three times more likely to develop TC than men [ 10 , 16 ].…”
Section: Introductionmentioning
confidence: 99%